The Impact of SPSS on Research Completion - Ramdani, Falikhah; Hilmiyah , Faridatul; Indriyani, Vina (The Future of Education Journal, 2025)
The aim of this research is to provide an in-depth analysis of the impact of SPSS software on the efficiency and accuracy of data analysis, particularly among students enrolled in statistics courses. As a leading statistical analysis tool, SPSS offers a range of features to integrate data management processes, statistical processing, and result visualization into one intuitive platform. This study is based on an experimental design with a population of statistics students, and data collection was conducted through direct observation and structured surveys. The analysis was performed using both descriptive and inferential statistical approaches to assess significant differences between the use of SPSS and manual methods in terms of speed, accuracy, and data presentation effectiveness. The study demonstrates that SPSS consistently provides faster and more accurate analysis results, while minimizing the risk of human error by automating calculation processes. Additionally, SPSS has proven to be superior in generating comprehensive data visualizations, making it easier to interpret and create reports. These findings highlight the important role of SPSS as a tool that not only enhances the quality of statistical learning but also prepares students to face data analysis challenges in the professional world.